If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6=-5x+2x
We simplify the equation to the form, which is simple to understand
6=-5x+2x
We move all terms containing x to the left and all other terms to the right.
+5x-2x=-6
We simplify left and right side of the equation.
+3x=-6
We divide both sides of the equation by 3 to get x.
x=-2
| 3x-24=2x+1 | | 26x+11x-1=0 | | 3x^3-21x^2=54x | | 4x^3-y=8 | | 7=(-3)-2w | | 3(x+1)-2(3x+7)=14 | | -8.5x-5y+12-3.5x-16= | | x^4+12x^3-8x^2=0 | | -8.5x-5y+12-3.5x= | | x^4+12x^3-45x^2=0 | | 3m+7.5= | | 0=-4t^2+24t | | x^4+7x^3-30x^2=0 | | x^2-10x+23=0 | | 19=(-2x)+4 | | 9-3p=8 | | 2x^2+50x+9=5 | | 4x^2-15x-97=0 | | 0.5x+19.3=x-5.55 | | 2x^2+693=4x | | 0.9x+2.64=-0.5x+0.64 | | x^3+5x^2-10x=0 | | 600x-0.32=400x+0.94 | | 9.7=8x+2.5 | | (4x-1)(x)=18 | | y-2.2=10 | | 4x-26.7=x | | 7(x-1.8)=7.7 | | 8.2y+6.99=-64.35 | | 3x+16=2x+10 | | 72x^4+132x^3-36x^2-24x=0 | | x+3.1=6.4 |